2016
DOI: 10.1177/0956462416674093
|View full text |Cite
|
Sign up to set email alerts
|

Late HIV presentation – missed opportunities and factors associated with a changing pattern over time

Abstract: Delayed diagnosis of HIV infection has negative clinical, economic and public health implications. The study primary aim was to identify factors associated with late HIV presentation (Late Presenters [LPS], CD4 cell count < 350 cells/mm). A secondary aim was to identify changing trends of late HIV presentation from 2002 to 2014 at our centre. A retrospective cohort study was performed. Demographic data and CD4 cell count of new HIV diagnoses presenting to our ambulatory HIV service over four time-periods from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Although the contribution of heterosexuals for HIV transmission is lower than that of gbMSMs, the findings reveal significantly higher LP prevalence among heterosexuals than in gbMSMs [adjusted OR (95% CI), 1.54 (1.40–1.70)] and an upward trend of LP among heterosexuals ( P for trend < 0.001); this warrants a critical rethink of the HIV prevention strategies for both heterosexuals and gbMSMs in Taiwan. The finding of higher LP prevalence among heterosexuals in the present study is consistent with findings from other studies [ 5 , 27 ], and may be attributable to the lower HIV testing rates among heterosexuals [ 28 ]. One explanation for this is the particular history of the HIV epidemic in Taiwan.…”
Section: Discussionsupporting
confidence: 93%
“…Although the contribution of heterosexuals for HIV transmission is lower than that of gbMSMs, the findings reveal significantly higher LP prevalence among heterosexuals than in gbMSMs [adjusted OR (95% CI), 1.54 (1.40–1.70)] and an upward trend of LP among heterosexuals ( P for trend < 0.001); this warrants a critical rethink of the HIV prevention strategies for both heterosexuals and gbMSMs in Taiwan. The finding of higher LP prevalence among heterosexuals in the present study is consistent with findings from other studies [ 5 , 27 ], and may be attributable to the lower HIV testing rates among heterosexuals [ 28 ]. One explanation for this is the particular history of the HIV epidemic in Taiwan.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, healthcare providers may consider HIV testing less often in individuals who are not perceived as being at high risk of HIV such as older individuals or heterosexuals, leading to missed opportunities for HIV diagnosis. High rates of missed opportunities for HIV diagnosis have previously been reported, highlighting the ongoing need for physician education on HIV testing and clinical signs suggestive of HIV infection 31 , 32 . This is particularly relevant for people aged 50 years since this group would benefit most from immediate initiation of ART as recently shown in a post-hoc subgroup analysis of the START trial 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in developed countries have demonstrated that non-traditional risk groups including women, heterosexual individuals and older adults are more likely to be tested later in the course of HIV infection [79]. These data provide important information for policy-making regarding HIV screening strategies in those settings.…”
Section: Introductionmentioning
confidence: 99%